1998
DOI: 10.1007/bfb0053008
|View full text |Cite
|
Sign up to set email alerts
|

BUILD-IT: An intuitive design tool based on direct object manipulation

Abstract: Natural interaction, in the context of this paper, means human action in a world of tangible objects and live subjects. We introduce the concept of action regulation and relate it to observable human behaviour. A tool bringing together motor and cognitive action is a promising way to assure complete task regulation. Aiming for such tools, we propose a set of guidelines for the next generation of user interfaces, the Natural User Interface (NUI). We present a NUI instantiation called BUILD-IT, featuring video-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 12 publications
0
30
0
2
Order By: Relevance
“…BUILD-IT is a planning tool based on state-of-the-art computer vision technology (Rauterberg et al, 1997a(Rauterberg et al, , 1997b(Rauterberg et al, , 1998Fjeld et al, 1998aFjeld et al, , 1998bFjeld et al, , 1998cFjeld et al, , 1999aFjeld et al, , 1999bFjeld et al, , 2000Fjeld et al, , 2001Fjeld, 2001). This system ( Figure 5) enables its users to cooperate in a virtual environment for planning a real-world object, such as a room, a school, a factory, or a piazza.…”
Section: Design Example: the Build-it Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…BUILD-IT is a planning tool based on state-of-the-art computer vision technology (Rauterberg et al, 1997a(Rauterberg et al, , 1997b(Rauterberg et al, , 1998Fjeld et al, 1998aFjeld et al, , 1998bFjeld et al, , 1998cFjeld et al, , 1999aFjeld et al, , 1999bFjeld et al, , 2000Fjeld et al, , 2001Fjeld, 2001). This system ( Figure 5) enables its users to cooperate in a virtual environment for planning a real-world object, such as a room, a school, a factory, or a piazza.…”
Section: Design Example: the Build-it Systemmentioning
confidence: 99%
“…Backed up by activity theory and the usage of AR, we developed groupware for layout planning and configuration tasks; this groupware is called the BUILD-IT system (Rauterberg et al, 1997a(Rauterberg et al, , 1997b(Rauterberg et al, , 1998Fjeld et al, 1998aFjeld et al, , 1998bFjeld et al, , 1998cFjeld et al, , 1999aFjeld et al, , 1999bFjeld et al, , 2000Fjeld et al, , 2001Fjeld, 2001). This system enables end-users, grouped around a table, to cooperate in the active design of a virtual setting, thus supporting co-located, instead of distributed, interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Using the BUILD-IT system as a research platform for graspable interaction [8], our exploration takes the following path: Section 2 introduces some of the problems related to working in real and virtual environments, then indicates a few guidelines to achieve what we call natural interaction. Section 3 gives more details about the interaction content, which is configuration and planning tasks.…”
Section: Fig 1 Build-it Consists Of a Rack Mirror Table Chairs Amentioning
confidence: 99%
“…Among others, this type of interaction was described by Ishii and Ullmer (1997), Underkoffler and Ishii (1998) and Fjeld, Bichsel and Rauterberg (1998). Rauterberg, Mauch and Stebler (1996) showed that a brick based interface is significantly easier and more intuitive to use than mouse and screen based interfaces.…”
mentioning
confidence: 94%
“…Finally, we describe some user experiences. In a first step, we have designed a partial Natural User Interface (NUI) instantiation (Figure 1), as described by Fjeld, Bichsel and Rauterberg (1998). Partial means that distributed communication between multiple systems has not yet been implemented.…”
mentioning
confidence: 99%